Turma da Mônica em : o processo de aprendizagem da língua portuguesa pela criança surda - Santos, Polyana Lacerda (2019)
This research has analized the teaching of Portuguese language, in the written modality, in reading and textual interpretation, for the deaf through the textual genre of the comic books of the Monica class. Used as a theoretical grounds authors like Bari; Goldfeld; Quadros; Silva; Souza; Vergueiro. The research was a descriptive qualitative basis, configured in a case study. The field investigated was a class of the 4th year of elementary School, located in Aracaju/SE city, having five students and one teacher. The analyzed data were produced based on participant observation and pedagogic activities performed in the classroom once a week. We also performed observations of the routines of the classes and recreations, compiled in the field diary, in addition to image records through photographs, audiotaped interviews with the teacher and pedagogical coordinator. The analysis of the data generated was performed through the assumptions of the content analysis (BARDIN). The data indicate that the comics when acting as a pedagogical tool, help deaf students in the teaching of Portuguese, allowing them a greater understanding of the process of reading, writing and textual interpretation, through the ludicity and the apparatus Existing visuals in stories, improving student performance and making reading attractive and accessible to children.